2019
DOI: 10.1080/13537113.2019.1602374
|View full text |Cite
|
Sign up to set email alerts
|

Identity Politics and Right-Wing Populism in Estonia: The Case of EKRE

Abstract: This case study focuses on Estonia and introduces the populist and radical right-wing party of EKRE (Eesti Konservatiivne Rahvaerakond/Estonian Conservative People's Party). It demonstrates that EKRE's employment of identity politics over the refugee question and immigration is embedded inside the pre-existing frame of Estonian restoration and "decolonization" nationalism. The party's campaign over the refugee question and immigration interlinks the collective memories of "colonization" under the Soviets with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…EKRE is often classified as a PRRP (Mudde 2016, p. 7; see also Braghiroli & Petsinis, 2019;Kasekamp et al, 2019;Petsinis, 2019) although, as our interviews indicate, the members prefer to see themselves as "national conservatives." Its ideology is based on nativism (an anti-Russian stance and anti-immigration sentiments), Euroscepticism, and the promotion of traditional family values.…”
Section: The Origins and Development Of Ekrementioning
confidence: 82%
“…EKRE is often classified as a PRRP (Mudde 2016, p. 7; see also Braghiroli & Petsinis, 2019;Kasekamp et al, 2019;Petsinis, 2019) although, as our interviews indicate, the members prefer to see themselves as "national conservatives." Its ideology is based on nativism (an anti-Russian stance and anti-immigration sentiments), Euroscepticism, and the promotion of traditional family values.…”
Section: The Origins and Development Of Ekrementioning
confidence: 82%
“…Some scholars argued that the results obtained in the elections are not under control and the management of different organisations was unable to monitor them. In an investigation presented by Petsinis (2019), it was argued that the results obtained by the management of different organisations showed that they were not obtaining the results. The analysis confirmed that two European crisis resulted in the development of low support for both Euro Scepticism and Right Wing Populism parties.…”
Section: Discussionmentioning
confidence: 99%
“…But this rather comfortable victory was not enough to secure the position of the Prime Minister (see below). The biggest winner of the election was the EKRE, a right-wing populist party (Petsinis 2019), which more than doubled it seat and vote shares, emerging as the third largest party in Parliament. It had entered Parliament in the previous election in 2015 with only seven seats together with the Estonian Free Party/Eesti Vabaerakond (EVA), another protest party (Mölder 2016), which, unlike the EKRE, had internally disintegrated by the 2019 elections and completely failed at the polls.…”
Section: Sotsiaaldemokraatlik Erakondmentioning
confidence: 99%